2016
DOI: 10.1080/00918369.2016.1244443
|View full text |Cite
|
Sign up to set email alerts
|

Is Gaydar Affected by Attitudes Toward Homosexuality? Confidence, Labeling Bias, and Accuracy

Abstract: Previous research has largely ignored the relationship between sexual orientation judgement accuracy, confidence, and attitudes towards homosexuality. In an online study, participants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
6
1
Order By: Relevance
“…The current findings cast doubt on the existence of an accurate auditory gaydar for female voice. This result is in contrast with findings on facial features, where the detection of SO for female targets was found to be quite accurate and better than for male targets (Brewer & Lyons, 2017; Lyons et al, 2014; Tabak & Zayas, 2012). This raises the interesting question of whether different cues may have distinct communicative meanings as well as different weights in revealing personal information such as SO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The current findings cast doubt on the existence of an accurate auditory gaydar for female voice. This result is in contrast with findings on facial features, where the detection of SO for female targets was found to be quite accurate and better than for male targets (Brewer & Lyons, 2017; Lyons et al, 2014; Tabak & Zayas, 2012). This raises the interesting question of whether different cues may have distinct communicative meanings as well as different weights in revealing personal information such as SO.…”
Section: Discussioncontrasting
confidence: 99%
“…One may argue that findings for male voices can be generalized to female voices. However, research on visual gaydar indicates that individuals are more accurate in judging women’s than men’s SO (Brewer & Lyons, 2017; Lyons, Lynch, Brewer, & Bruno, 2014; Tabak & Zayas, 2012). At the same time, it is commonly believed that people are better at recognizing gay men than lesbian women using voice cues (Fasoli, Hegarty, Maass, & Antonio, 2018) and, when judging SO, they are more prone to label a man as gay than to label a woman as lesbian (Lyons et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We considered three dimensions of essentialist beliefs about auditory gaydar; the use of vocal cues to infer others' SO. Research has considered whether heterosexuals' prejudice predicts SO categorization and accuracy (Brewer & Lyons, 2017;Rule et al, 2015), but not how essentialist beliefs about SO cues relate to prejudice and stigma. As Gertler and Thorpe (2014) documentary makes clear, belief in auditory gaydar presumes voice discreteness; the belief that LG and heterosexual speakers have categorically different voices.…”
Section: Voice-based Essentialist Beliefsmentioning
confidence: 99%
“…Here, heterosexual and non‐heterosexual perceivers showed equivalent levels of accuracy. In multiple previous studies, however, gay and lesbian perceivers demonstrated greater sensitivity to others’ self‐identified sexual orientation than heterosexual perceivers did (Johnson & Ghavami, 2011; Rule et al., 2007; but see also Brewer & Lyons, 2017). Speculating, we wonder whether the particularly intergroup nature of thinking about sexual orientation in terms of categories (vs. as a continuum of attraction, as done here) may help to stimulate the group‐based thinking necessary to lead to a minority‐group advantage.…”
Section: Discussionmentioning
confidence: 85%